Portable Ramp for Special Needs Student in Primary School - Siti Salbiah Ahmad Shariff; Nazleena Daud; Mohd Halid Abu (Nusantara Civil Engineering Journal, 2025)
This study focused on designing and implementing a portable ramp to enhance accessibility for wheelchair-using students special needs at sekolah Kebangsan Cheng, Melaka and Sekolah kebangsaan Bukit China, Melaka. Students and teachers faced difficulties accessing areas like canteens, classrooms, and assembly halls due to architectural barriers such as stairs and uneven terrain. Many schools lack permanent infrastructure to support mobility-impaired students special needs, limiting their participation. The portable ramp was developed as a safe, reliable, and convenient solution for overcoming these obstacles. It facilitates smooth transitions between elevations, ensuring ease of movement and addressing mobility challenges. Field tests and questionnaires were conducted to assess the ramp’s durability and effectiveness. Teachers and student assistants participated in pre- and post-test evaluations to measure their understanding of the ramp's use, complemented by a practical demonstration of its setup. User feedback and testing revealed that Ramp-On effectively improved accessibility and safety in school settings. While some areas for enhancement were noted, the majority of responses were positive, affirming the ramp’s success in meeting the needs of primary school students special needs with mobility impairments.